Effect of Si/Al molar ratio on zeolite synthesis from nipah leaf and used canned aluminium - Rizkia Putri, Arsita Nur; Fadlilah, Ilma; Prasadi, Oto (Universitas Lambung Mangkurat, 2023)
Silica and alumunium are the main sources in the manufacture of synthetic zeolite which will be engineered in such a way that it contains the same character as natural zeolite. The silica content in Nipah leaf waste is 26,28 % and the alumunium content in used cans is 53,09 %, it has the potential to be the main ingredient in zeolite synthesis. This study aims to determine the effect of Si/Al molar ratio on synthetic zeolite characteristics. Making zeolite is done by mixing silica and alumunium as well as the zeolite crystallization process using a hydrothermal reactor. Characterization of zeolite was carried out by morphological analysis and elemental composition using SEM-EDX and functional group analysis using FTIR. The results of SEM-EDX show the morphology and composition of zeolite forming elements included in low sillica zeolite, and FTIR results show functional groups of synthetic zeolite in the form of double rings at wavevumbers 500 – 650 cm-1, and the presence of zeolite finger prints at wavenumbers 700 – 1100 cm-1.